Antimony-doped cesium tungsten bronze nano-powder and preparation method thereof
By adding antimony into cesium tungsten bronze and using solid phase method and ball milling refining process, antimony-doped cesium tungsten bronze nanopowder was prepared, which solved the problem of large material particle size and difficulty in nano-narrowing, and achieved high-performance and uniform size preparation of nanopowders, suitable for industrial production and transparent heat insulation applications.
Patent Information
- Application Number
- CN202411812491.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-21
AI Technical Summary
During the preparation process, the existing cesium tungsten bronze materials have problems such as large particle size and difficulty in breaking into nano-scale powders. The reaction solvents used in the solvothermal method are harmful to the environment and are difficult to achieve large-scale industrial production.
By adding an appropriate amount of antimony to the cesium tungsten bronze, combined with solid phase method and ball milling refinement technology, antimony-doped cesium tungsten bronze nanopowder was prepared, which achieved the uniformization of the particle size of the material and the improvement of the breaking ability.
It achieves high performance and dimensional uniformity of cesium tungsten bronze nanopowder, is suitable for large-scale industrial preparation, improves the visible light transmittance and near-infrared shielding of the material, and is suitable for transparent thermal insulation coatings.
Smart Images

Figure CN119660801A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an antimony-doped cesium tungsten bronze nano powder and a preparation method thereof, belonging to the technical field of cesium tungsten bronze materials. Background Art
[0002] Windows are the main channel for energy exchange between buildings and the outside world. A large amount of infrared heat radiation enters the room through transparent surfaces such as windows, causing the temperature inside the building to rise rapidly. Improving the thermal insulation performance of building windows is an effective way to reduce building cooling energy consumption.
[0003] Cesium tungsten bronze (Cs x WO3) has excellent infrared shielding and visible light transmittance properties, and has broad application prospects in the field of near-infrared shielding window materials. Cesium tungsten bronze has a variety of different preparation methods: the solid phase method is a common method for synthesizing cesium tungsten bronze. This method has the advantages of high yield, simple operation, and high efficiency, but the reaction conditions are relatively harsh. It generally needs to be carried out in a high-temperature reducing atmosphere, and the product particle size is large, and it is difficult to break it into uniformly sized nano-scale powders; the liquid phase method includes hydrothermal method, solvent thermal method and sol-gel method, which are characterized by simple operation and relatively controllable size and morphology, but the hydrothermal method has a long reaction time, low yield, and the high pressure during the reaction process has certain safety hazards, which is not suitable for large-scale industrial production.
[0004] Chinese patent application CN114853068A discloses a titanium-doped cesium tungsten bronze powder and a preparation method thereof. By doping an appropriate amount of Ti into the cesium tungsten bronze and using a solvent method to prepare the powder, the visible light transmittance and infrared shielding performance of the material are significantly improved. However, the reaction solvent required for the solvothermal method may be harmful to the environment, causing difficulties in subsequent treatment. In addition, in the process of preparing the doped product by the solvothermal method, it is difficult to accurately control the doping ratio and output, and industrial mass production cannot be achieved. At the same time, Ti doping is difficult to improve the problem of large particle size of cesium tungsten bronze powder, which is not conducive to practical application. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide an antimony-doped cesium tungsten bronze nanopowder and a preparation method thereof. By adding an appropriate amount of antimony to cesium tungsten bronze, on the one hand, the visible light transmittance and infrared shielding rate of the nanomaterial are improved, and it has great application potential in the field of window transparent heat insulation film; on the other hand, the introduction of antimony improves the breaking ability of cesium tungsten bronze nanopowder, which is conducive to the mass preparation of cesium tungsten bronze nanopowder with uniform and fine size through a simple solid phase sintering method for industrial scale production.
[0006] To achieve the above objectives, the technical solution of the present invention is as follows.
[0007] A method for preparing antimony-doped cesium tungsten bronze nanopowder, the method steps comprising:
[0008] (1) Preparation of precursor: According to the atomic ratio of antimony element to the sum of antimony and tungsten elements being (0.01-0.1):1, and the atomic ratio of cesium element to the sum of antimony and tungsten elements being (0.3-0.35):1, a tungsten source, a cesium source, and an antimony source are fully ground and mixed to obtain a precursor;
[0009] (2) Sintering: The precursor is placed in a tube furnace and sintered in a mixed atmosphere of H2 and N2. The sintering temperature is 550-650°C and the holding time is 60-120 min. After the sintering is completed, a sintered product is obtained.
[0010] (3) Annealing: annealing the sintered product in a protective gas atmosphere to obtain a powder product;
[0011] (4) Ball milling: The powder product is ball milled at a speed of 230 to 280 r / min for 16 to 18 h. After the ball milling, vacuum drying is performed to obtain an antimony-doped cesium tungsten bronze powder.
[0012] Preferably, in step (1), the atomic ratio of antimony element to the sum of antimony and tungsten elements is (0.03-0.05):1.
[0013] Preferably, in step (1), the antimony source is antimony pentoxide, the tungsten source is tungsten trioxide or tungstic acid, and the cesium source is cesium carbonate, cesium sulfate or cesium hydroxide.
[0014] Preferably, in step (2), the volume ratio of H2 to N2 is 1 to 2:20.
[0015] Preferably, in step (2), the heating rate during sintering is 3 to 5° C. / min.
[0016] Preferably, in step (3), the annealing temperature is 400-600° C., and the holding time is 90-150 min.
[0017] Preferably, in step (3), the protective gas is nitrogen or an inert gas (a gas element corresponding to all Group 0 elements on the periodic table).
[0018] Preferably, in step (4), during ball milling, ethanol is added to perform wet ball milling.
[0019] Preferably, in step (4), the vacuum drying temperature is 60-80° C. and the time is 6-8 h.
[0020] An antimony-doped cesium tungsten bronze nanopowder with the chemical formula Cs x Sb y W 1-yO3, 0.30≤x≤0.35, 0.01≤y≤0.1, the nano powder is prepared by the above method, and the particle size of the nano powder is 50-100 nm.
[0021] Beneficial Effects
[0022] The present invention replaces part of tungsten atoms by doping element antimony, which can improve the near-infrared shielding and visible light transmittance of the powder while improving the breaking ability of the sintered product, which is conducive to obtaining small-particle nanopowders with uniform size through solid-phase method and ball milling, and realizes the industrial large-scale preparation of high-performance, uniform-sized small-particle cesium tungsten bronze powder.
[0023] In the process of preparing antimony-doped cesium tungsten bronze powder by the solid phase method of the present invention, by adjusting the sintering and ball milling process parameters, it can be ensured that the material has good crystallinity and the average size of the nanoparticles can be freely adjusted, and a powder material with good visible light transmittance and near-infrared shielding rate can be obtained for transparent thermal insulation coatings; by changing the proportion of antimony in the precursor, the visible light transmittance and near-infrared shielding rate of the material film can be further adjusted to meet different usage requirements.
[0024] In the present invention, the addition of antimony can affect the optical band gap of the product. As the amount of antimony added increases, the optical band gap of the product will change accordingly. By adjusting the antimony content in the precursor, the intrinsic absorption of the powder to visible light can be regulated; at the same time, the appropriate amount of antimony added enhances the photothermal conversion ability of the cesium tungsten bronze nanopowder, which can be expanded to the fields of photocatalysis, photothermal therapy, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The XRD patterns of the products obtained in Examples 1-4 and Comparative Examples are shown in FIG.
[0026] Figure 2 This is a scanning electron microscope image of the powder prepared under 18h ball milling conditions in the comparative example.
[0027] Figure 3 This is the SEM spectrum of the powder prepared under 18h ball milling conditions in Example 4.
[0028] Figure 4 This is the SEM spectrum of the powder prepared under 24h ball milling conditions in the comparative example.
[0029] Figure 5 It is the full XPS spectrum of the powders prepared in Examples 1-4 and the comparative example.
[0030] Figure 6 This is the high-resolution XPS spectrum of the W element in the powder prepared in the comparative example.
[0031] Figure 7This is a high-resolution XPS spectrum of the W element in the powder prepared in Example 2.
[0032] Figure 8 The UV-Vis-NIR spectra of the powders prepared in Examples 1-4 and Comparative Example.
[0033] Fig. 9 The optical band gap variation trend diagram of the powders prepared in Examples 1-4 and Comparative Example.
[0034] Fig.10 These are temperature images recorded by an infrared camera at room temperature for the powders prepared in Examples 1-4 and Comparative Example.
[0035] Fig.11 The infrared temperature change images of the powders prepared in Examples 1-4 and Comparative Example recorded by an infrared camera after being irradiated with an infrared lamp with a power of 150 W for 120 seconds. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with the accompanying drawings in the embodiments of the present invention, wherein the embodiments described are only a part of the embodiments of the present invention, and the methods are conventional methods unless otherwise specified. The specific embodiments described herein are only used to explain the present invention and are not limited to the present invention.
[0037] The following are the test characterization conditions used in the examples:
[0038] XRD test: The material was tested using a multifunctional X-ray diffractometer, SmartLab SE, from Rigaku. The ray source was Cu-Kα, the step length was 0.01°, and the diffraction peaks within the range of 10° to 80° were tested. The identification of the phase and the crystal structure information were analyzed using JADE 6.0 software.
[0039] SEM test: A Hitachi SU8230 field emission scanning electron microscope was used to observe the microscopic morphology of the material;
[0040] XPS test: The XPS instrument model is PHIQUANTERA-II SXM, the X-ray source is Al-Kα, and the photon energy is 1486.6 eV. The test peaks are all corrected by the standard C1s (E=284.8 eV) peak.
[0041] Optical transmittance test: The test was performed using a UV-Vis-NIR spectrophotometer (Cary 5000, Agilent Ltd.) with a wavelength range of 300 nm to 3000 nm.
[0042] Infrared thermal imaging detection: Use the A310 infrared camera produced by FLIR, with a detection wavelength range of 8-14μm and a detection accuracy of ±0.2℃.
[0043] Example 1
[0044] Weigh 0.1228g Cs2CO3, 0.5757g WO3 and 0.0038g Sb2O5 into a mortar, add a small amount of anhydrous ethanol and grind thoroughly to obtain a precursor with a molar ratio of cesium ion to the sum of antimony and tungsten ions of 0.32:1 and a molar ratio of antimony ion to the sum of antimony and tungsten ions of 0.01:1; transfer the precursor to a tube furnace, sinter at 5°C / min to 600°C in a H2 / N2 mixed atmosphere (H2 volume fraction is 5%) for 90min to form a phase, and cool with the furnace after sintering; introduce nitrogen into the tube furnace, anneal the powder product at 500°C and 60min. After annealing, place the product in a ball mill, add a small amount of anhydrous ethanol and ball mill at 250r / min for 18h. Take out the ball milled sample-ethanol mixture and place it in a vacuum oven at 60℃ for 12h to obtain 1at% antimony-doped cesium tungsten bronze powder, the chemical formula of which is abbreviated as Cs 0.32 W 0.99 Sb 0.01 O3.
[0045] Example 2
[0046] Weigh 0.1234g Cs2CO3, 0.5373g WO3 and 0.0116g Sb2O5 into a mortar, add a small amount of anhydrous ethanol and grind thoroughly to obtain a precursor with a molar ratio of cesium ion to the sum of antimony and tungsten ions of 0.32:1 and a molar ratio of antimony ion to the sum of antimony and tungsten ions of 0.03:1; transfer the precursor to a tube furnace, sinter at 5°C / min to 600°C in a 5% H2 / N2 mixed atmosphere for 90 minutes to form a phase, and cool with the furnace after sintering; introduce nitrogen into the tube furnace, anneal the powder product at 500°C and 60 minutes. After annealing, place the product in a ball mill, add a small amount of anhydrous ethanol, and ball mill at 250r / min for 18 hours. Take out the ball milled sample-ethanol mixture and place it in a vacuum oven at 60℃ for 12h to obtain 3at% antimony-doped cesium tungsten bronze powder, the chemical formula of which is abbreviated as Cs 0.32 W 0.97 Sb 0.03 O3.
[0047] Example 3
[0048] Weigh 0.1244g Cs2CO3, 0.5288g WO3 and 0.0193g Sb2O5 into a mortar, add a small amount of anhydrous ethanol and grind thoroughly to obtain a precursor with a molar ratio of cesium ion to the sum of antimony and tungsten ions of 0.32:1 and a molar ratio of antimony ion to the sum of antimony and tungsten ions of 0.05:1; transfer the precursor to a tube furnace, sinter at 5°C / min to 600°C in a 5% H2 / N2 mixed atmosphere for 90 minutes to form a phase, and cool with the furnace after sintering; introduce nitrogen into the tube furnace, anneal the powder product at 500°C and 60 minutes. After annealing, place the product in a ball mill, add a small amount of anhydrous ethanol, and ball mill at 250r / min for 18 hours. Take out the ball milled sample-ethanol mixture and place it in a vacuum oven at 60℃ for 12h to obtain 5at% antimony-doped cesium tungsten bronze powder, the chemical formula of which is abbreviated as Cs 0.32 W 0.95 Sb 0.05 O3.
[0049] Example 4
[0050] Weigh 0.1256g Cs2CO3, 0.5074g WO3 and 0.0390g Sb2O5 into a mortar, add a small amount of anhydrous ethanol and grind thoroughly to obtain a precursor with a molar ratio of cesium ion to the sum of antimony and tungsten ions of 0.32:1 and a molar ratio of antimony ion to the sum of antimony and tungsten ions of 0.1:1; transfer the precursor to a tube furnace, sinter at 5°C / min to 600°C in a 5% H2 / N2 mixed atmosphere for 90 minutes to form a phase, and cool with the furnace after sintering; introduce nitrogen into the tube furnace, anneal the powder product at 500°C and 60 minutes. After annealing, place the product in a ball mill, add a small amount of anhydrous ethanol, and ball mill at 250r / min for 18 hours. Take out the ball milled sample-ethanol mixture and place it in a vacuum oven at 60℃ for 12h to obtain 10at% antimony-doped cesium tungsten bronze powder, the chemical formula of which is abbreviated as Cs 0.32 W 0.90 Sb 0.10 O3.
[0051] Comparative Example
[0052] Weigh 0.1225g Cs2CO3 and 0.5598g WO3 into a mortar, add a small amount of anhydrous ethanol and grind thoroughly to obtain a precursor with a molar ratio of cesium ions to tungsten ions of 0.32:1; transfer the precursor to a tubular furnace, sinter at 5°C / min to 600°C for 90 minutes in a 5% H2 / N2 mixed atmosphere, and cool with the furnace after sintering; introduce nitrogen into the tubular furnace, anneal the powder product at 500°C and 60 minutes. After annealing, place the product in a ball mill, add ball mill beads, add a small amount of anhydrous ethanol, and ball mill at 250r / min for 18 hours. Take out the ball-milled sample-ethanol mixture and place it in a vacuum oven at 60°C for 12 hours to obtain cesium tungsten bronze powder, the chemical formula of which is abbreviated as Cs 0.32 WO3.
[0053] Figure 1 The XRD patterns of the products obtained in Examples 1-4 and Comparative Examples are shown in Figure 1. It can be seen from the figure that the diffraction peaks of the prepared powders are consistent with the hexagonal phase Cs 0.32 The characteristic peaks of the XRD standard card of WO3 (PDF#83-1334) are consistent, indicating that the crystal structure of the cesium tungsten bronze powder is not changed after the addition of antimony, and the powder has high purity and good crystallinity.
[0054] Figure 2 and Figure 3 The following are SEM spectra of the powders prepared under the same ball milling conditions in the comparative example and embodiment 4, respectively. Figure 2 , 3 It can be seen that the products of Example 4 and the comparative example are composed of nanoparticles with relatively uniform size distribution. When 10at% Sb is added to cesium tungsten bronze, the average particle size is reduced from 151nm in the comparative example to 58nm. The particle size distribution of the product becomes more uniform with the substitution of Sb and the average particle size of the nanoparticles gradually decreases. This shows that the sample is easier to break during ball milling after Sb doping, which is conducive to obtaining uniform-sized small-particle nanopowders through conventional solid-phase methods and ball milling refinement, and realizing the industrial large-scale preparation of high-performance, uniform-sized small-particle cesium tungsten bronze powders. In addition, for transparent thermal insulation coatings, particle sizes much smaller than the wavelength of visible light can reduce the coating's scattering of visible light, reduce haze, and thus improve visible light transmittance.
[0055] Figure 4 The SEM spectrum of the powder prepared by ball milling for 24 hours is shown in the comparative example. The average particle size is reduced to the same level as that of Example 4, which shows that after adding a small amount of 10at% Sb, the ball milling time required to obtain fine nanoparticles of similar size is reduced by 1 / 3, which greatly accelerates the production efficiency of fine nanopowders with high performance.
[0056] Figure 5The XPS full spectra of the powders prepared in Examples 1 to 4 and the comparative example are shown in Figure 1. Five elements, C, Cs, W, O, and Sb, can be observed in Examples 1 to 4, where the C element comes from the adsorbed carbon during the test.
[0057] Figure 6 This is a high-resolution XPS spectrum of the W element in the powder prepared in the comparative example. 6+ and W 5+ The mixed valence form appears, where W 6+ The content is 76.48%, W 5+ The content is 22.52%.
[0058] Figure 7 : is a high-resolution XPS spectrum of the W element in the powder prepared in Example 2. As can be seen from the figure, the W element in the embodiment is W 6+ and W 5+ The mixed valence form appears, where W 6+ The content is 81.80%, W 5+ The content is 18.20%. This shows that when the relatively low-priced Sb 5+ Doping to replace expensive W 6+ Finally, in order to maintain the overall electrical neutrality, part of the W in the cesium tungsten bronze 5+ Convert to W 6+ .
[0059] Figure 8 The solar spectrum transmittance (UV-Vis-NIR spectrum) after the prepared powder (Examples 1-4, comparative example) slurry is spin-coated on a glass substrate to form a film. Obviously, the maximum visible light transmittance of the Sb-doped cesium tungsten bronze composite film can reach 83%. At the same time, the integrated transmittance in the entire visible light region (380-780nm) exceeds 60%, reaching the applicable optical film transmittance standard, and the average integrated shielding rate in the near-infrared region (780-2500nm) is as high as 65%. Compared with the comparative example (undoped sample) film, it can be considered that with the incorporation of Sb, the light transmittance of the film is enhanced and the near-infrared shielding rate is increased. In summary, Cs x Sb y W 1-y O3 powder has good transparent heat insulation performance. When used as a coating for building windows, it can shield most of the thermal infrared rays while ensuring daylighting, maintaining a stable indoor temperature. The visible light integral transmittance and near infrared integral shielding rate of the comparative example are 57.7% and 57% respectively; the visible light integral transmittance of Examples 1-4 are 61.9%, 65.9%, 65.5%, and 64.7% respectively, and the near infrared integral shielding rates are 65.1%, 70%, 69.8%, and 65.7% respectively.
[0060] Fig. 9The trend diagram of the optical band gap change of the powder prepared in Examples 1-4 and Comparative Example 1. The change in the optical band gap causes the intrinsic absorption edge of the material to blue-shift from 546nm of the comparative example product to 481nm of the product of Example 2 (the band gaps under light of Examples 1-4 are 2.31eV, 2.58eV, 2.52eV, and 1.93eV, respectively, and the corresponding intrinsic absorption edges are 537nm, 481nm, 492nm, and 642nm, respectively). Examples 1-3 reduce the absorption of visible light by Sb-doped powders and enhance visible light transmittance. At the same time, by adjusting the amount of Sb added, the selective absorption of the product powder to the visible light band can be achieved.
[0061] Fig.10 The infrared temperature images of the powders prepared in Examples 1-4 and Comparative Examples recorded by an infrared camera at room temperature. In a room without direct infrared light, the initial temperatures of the standard infrared KBr pellets, Comparative Examples, and Examples 1-4 are close, which are 22.7°C, 21.5°C, 21.8°C, 21.6°C, 21.7°C, and 21.7°C, respectively.
[0062] Fig.11 The infrared temperature change images of the powders prepared in Examples 1-4 and Comparative Examples recorded by an infrared camera after being irradiated with an infrared lamp with a power of 150W for 120s. At this time, the temperatures of the standard infrared KBr tablets without strong infrared heat absorption and the comparative examples and Examples 1-4 showed obvious differences, which were 30.4°C, 37.9°C, 38.7°C, 40.8°C, 43.0°C, and 43.2°C, respectively. Since the infrared shielding ability of cesium tungsten bronze is attributed to the surface plasmon resonance and small polaron transition absorption, the absorbed infrared light is converted into heat dissipation, so cesium tungsten bronze has a certain light-to-heat conversion ability. In the temperature change diagram recorded by the infrared camera, compared with the undoped Cs 0.32 WO3 powder (37.9℃), because Sb-doped cesium tungsten bronze nanopowder has stronger infrared absorption ability and thus exhibits stronger infrared absorption heat conversion ability, it has the potential to be used in the fields of photocatalysis and photothermal therapy.
[0063] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A method for preparing antimony-doped cesium tungsten bronze nanopowder, characterized in that: The method steps include: (1) According to the atomic ratio of antimony element to the sum of antimony and tungsten elements being (0.01-0.1):1, and the atomic ratio of cesium element to the sum of antimony and tungsten elements being (0.3-0.35):1, a tungsten source, a cesium source, and an antimony source are fully ground and mixed to obtain a precursor; (2) placing the precursor in a tube furnace and sintering it in a mixed atmosphere of H2 and N2 at a sintering temperature of 550 to 650°C for a holding time of 60 to 120 minutes to obtain a sintered product after the sintering is completed; (3) annealing the sintered product under a protective gas atmosphere to obtain a powder product; (4) The powder product is ball-milled at a ball-milling speed of 230 to 280 r / min for a ball-milling time of 16 to 18 h. After the ball-milling, vacuum drying is performed to obtain an antimony-doped cesium tungsten bronze powder.
2. The method for preparing antimony-doped cesium tungsten bronze nanopowder according to claim 1, characterized in that: In step (1), the atomic ratio of antimony element to the sum of antimony and tungsten elements is (0.03-0.05):
1.
3. The method for preparing antimony-doped cesium tungsten bronze nanopowder according to claim 1, characterized in that: In step (1), the antimony source is antimony pentoxide, the tungsten source is tungsten trioxide or tungstic acid, and the cesium source is cesium carbonate, cesium sulfate or cesium hydroxide.
4. The method for preparing antimony-doped cesium tungsten bronze nanopowder according to claim 1, characterized in that: In step (2), the volume ratio of H2 to N2 is 1 to 2:
20.
5. The method for preparing antimony-doped cesium tungsten bronze nanopowder according to claim 1, characterized in that: In step (2), the heating rate during sintering is 3 to 5°C / min.
6. The method for preparing antimony-doped cesium tungsten bronze nanopowder according to claim 1, characterized in that: In step (3), the annealing temperature is 400-600° C., and the holding time is 90-150 min.
7. The method for preparing antimony-doped cesium tungsten bronze nanopowder according to claim 1, characterized in that: In step (3), the protective gas is nitrogen or an inert gas.
8. The method for preparing antimony-doped cesium tungsten bronze nanopowder according to claim 1, characterized in that: In step (4), during ball milling, ethanol is added to perform wet ball milling.
9. The method for preparing antimony-doped cesium tungsten bronze nanopowder according to claim 1, characterized in that: In step (4), the vacuum drying temperature is 60 to 80° C. and the time is 6 to 8 hours. 10.An antimony-doped cesium tungsten bronze nanopowder, characterized in that: The chemical formula is Cs x Sb y W 1-y O3, 0.30≤x≤0.35, 0.01≤y≤0.1, the nano powder is prepared by the method according to any one of claims 1 to 9, and the particle size of the nano powder is 50 to 100 nm.
Citation Information
Patent Citations
Titanium-doped cesium tungsten bronze powder and preparation method thereof
CN114853068A